Design a cryptosystem using elliptic curves cryptography and Vigenère symmetry key - Mai Manh Trung; Le Phe Do; Do Trung Tuan; Nguyen Van Tanh; Ngo Quang Tri (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this paper describes the basic idea of elliptic curve cryptography (ECC) as well as Vigenère symmetry key. Elliptic curve arithmetic can be used to develop elliptic curve coding schemes, including key exchange, encryption, and digital signature. The main attraction of elliptic curve cryptography compared to Rivest, Shamir, Adleman (RSA) is that it provides equivalent security for a smaller key size, which reduces processing costs. From the theorical basic, we proposed a cryptosystem using elliptic curves and Vigenère cryptography. We proposed and implemented our encryption algorithm in an integrated development environment named visual studio 2019 to design a safe, secure, and effective cryptosystem.